Effect of seed revitalization techniques on some biomarkers of wheat seed growth (Texas Journal of Agriculture and Biological Sciences, 2023)
A laboratory experiment was carried out during the agricultural season 2022-2023 to identify the response of seeds of two bread wheat cultivars (Abo-Raghif - Al-Forat) to some techniques of stimulating germination treatments. The number of these treatments was 4 (soaking for one hour in water - soaking for two hours - treating the seeds with gibberellin Before planting - treating seeds with boron before planting). The laboratory experiment was carried out according to the experimental design (CRD) with three replications. The results of the experiment were summarized as follows: The cultivar Abo-Raghif was significantly superior in most of the studied traits to the cultivar Forat, as it recorded the highest mean for the traits (germination percentage, root length, stem length, seedling strength) was (90.00% - 5.75 cm78.50cm- 1246.9)) in sequence. The variety Forat excelled in the speed of germination, recording 75.4%. As for the treatments for activating seed germination, the treatment of seeds with gibberellin was superior in all the studied characteristics (germination speed, germination rate, root length, shoot length, seedling strength), recording the highest rates, as it reached (83.3% - 91.67% -71.67 cm - 86.83 cm - 14.53.3) sequentially. The bilateral interaction between the Abo-Raghif variety and the gibberellin treatment had significant superiority in most of the studied traits over most of the other combinations.